HYDRA (MULTIPURPOSE HYBRID DRYER) SYSTEM FOR HYBRID DRYER ENERGY EFFICIENCY - Muhimatul Ulya Mukasafah; Desy Syfa Urrohmah; Hizar Alhifari Ramadhan; Mochammad Takbirul Id’ha; Deo Farma Alhadi (Journal of the Community Development in Asia (JCDA), 2018)
The purpose of this research is to provide solutions to the problems of SMES in Kampong Nambangan Kenjeran West about the process of drying fish that are conventional and long drying time. The method was designed to resemble a house that has 3 shelves made from Food Grade and a house wall made from acrylic transfaran, with a hybrid energy system that is sunlight and Infra red stove made from LPG Gas Fuel. This machine integrates ECU (Electrical Control Unit) technology. The results with a hybrid drying system can improve the drying process faster up to 3 times, The productivity increased from 25kg/day to 50 kg/day.